2022
DOI: 10.3389/fbioe.2022.819148
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Cocktails-Based Strategy in Culture of Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) have a variety of unique properties, such as stem cell multipotency and immune regulation, making them attractive for use in cell therapy. Before infusion therapy, MSCs are required to undergo tissue separation, purification, and expansion in vitro for a certain duration. During the process of in vitro expansion of MSCs, the influence of culture time and environment can lead to cell senescence, increased heterogeneity, and function attenuation, which limits their clinical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Many studies reported the optimal combination of cytokines could improve the therapeutic effect of MSC, such as TNF-α and IFN-γ ( 44 ), IL-10 ( 45 ), HGF ( 46 ), or IDO ( 47 ). Our previous study also found that a cocktail of small-molecule compounds SM-ACY could improve the growth of MSCs ( 23 ). Moreover, we further discovered that SM-ACY which involving in three different signaling pathways respectively were capable to enhance the immunoregulatory effects of MSCs in vitro/vivo .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Many studies reported the optimal combination of cytokines could improve the therapeutic effect of MSC, such as TNF-α and IFN-γ ( 44 ), IL-10 ( 45 ), HGF ( 46 ), or IDO ( 47 ). Our previous study also found that a cocktail of small-molecule compounds SM-ACY could improve the growth of MSCs ( 23 ). Moreover, we further discovered that SM-ACY which involving in three different signaling pathways respectively were capable to enhance the immunoregulatory effects of MSCs in vitro/vivo .…”
Section: Discussionmentioning
confidence: 87%
“…Following the Clinical Research Ethics Committee of the Third Affiliated Hospital of Sun Yat-sen University and written informed patient consent for tissue collection, MSCs were isolated following the protocol described in the previous study ( 23 ). In brief, fat tissues were isolated via liposuction from healthy patients defined as no history of malignancy or autoimmune deficiency.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Y-27632 is a ROCK inhibitor [ 21 ], A-83-01 is an inhibitor of transforming growth factor-β (TGF-β) signaling [ 22 ], and CHIR99021 is an activator of Wnt signaling via inhibition of glycogen synthase kinase-3 [ 23 ]. YAC has been utilized in various combinations to culture human stem cells [ 24 ], and previous studies used at least one of these inhibitors to maintain proliferation of primary human AECIIs [ 11 , 12 , 25 ]. We obtained primary human AECs and initially cultured them in flasks containing medium supplemented with YAC under submerged conditions, followed by culturing at the air-liquid interface (ALI).…”
Section: Introductionmentioning
confidence: 99%